Implementasi Aplikasi Dalam Peningkatan Penjualan Batik Di PT. Pedjoeang Batik - Lubis, Zulham Wahyudi; Ridho , Faizin (Innovative: Journal Of Social Science Research, 2024)
In today's digital era, the need for information is increasing, especially in the business world. PT Pedjoeang Batik seeks to introduce Batik Tulis to the international market by developing a web-based application. This study uses Waterfall's qualitative methods and systematic approach to understand how digital promotion strategies are implemented and design promotional applications. The results show that this application not only improves visibility and brand image, but also simplifies data management and improves operational efficiency. This finding is an important contribution for MSMEs, especially in marketing unique products such as batik in the global market. For further research, it is recommended that new technologies be explored to improve user interaction and experience.